2013
DOI: 10.1002/jbmr.1877
|View full text |Cite
|
Sign up to set email alerts
|

The P2Y13 receptor regulates extracellular ATP metabolism and the osteogenic response to mechanical loading

Abstract: ATP release and subsequent activation of purinergic receptors has been suggested to be one of the key transduction pathways activated by mechanical stimulation of bone. The P2Y 13 receptor, recently found to be expressed by osteoblasts, has been suggested to provide a negative feedback pathway for ATP release in different cell types. Therefore, we hypothesized that the P2Y 13 receptor may contribute to the mediation of osteogenic responses to mechanical stimulation by regulating ATP metabolism by osteoblasts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…We, and others, have shown that the P2X 7 receptor enhances proliferation, ERK1/2 phosphorylation, and COX-2 production in osteoblasts (24,31), and that knockout of this receptor significantly attenuates load-induced bone formation in vivo (29). In contrast, P2Y 2 R and P2Y 13 R knockout mice exhibit excessive bone formation in response to mechanical loading (40,56), demonstrating that these receptors inhibit the anabolic response of bone. Based on our results, the increased bone formation in the P2Y 2 R knockout mice under dynamic loading (40) may be explained by the increased mechanosensitivity due to a lack of ASFF to downregulate the osteoblasts sensitivity to mechanical stimuli.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We, and others, have shown that the P2X 7 receptor enhances proliferation, ERK1/2 phosphorylation, and COX-2 production in osteoblasts (24,31), and that knockout of this receptor significantly attenuates load-induced bone formation in vivo (29). In contrast, P2Y 2 R and P2Y 13 R knockout mice exhibit excessive bone formation in response to mechanical loading (40,56), demonstrating that these receptors inhibit the anabolic response of bone. Based on our results, the increased bone formation in the P2Y 2 R knockout mice under dynamic loading (40) may be explained by the increased mechanosensitivity due to a lack of ASFF to downregulate the osteoblasts sensitivity to mechanical stimuli.…”
Section: Discussionmentioning
confidence: 87%
“…P2 receptors are classified as G protein-coupled receptors P2Y (P2Y 1,2,4,6,11,12,13,14 ) or nonselective, ligand-gated ion channels P2X (P2X 1-7 ) (39). The P2Y 2 R and P2Y 13 R knockout mice have both been shown to increase trabecular and cortical bone formation to dynamic loading, which suggests a negative regulation by the P2Y receptor in bone formation (40,56). The negative feedback associated with the P2Y 13 R is thought to be mediated by excessive ATP release (56).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other receptors are also emerging to play a role in the balance of MSC differentiation to bone, including the P2Y 13 receptor [7]. Interestingly, the P2Y 13 receptor could possibly play a role in the mechanism of release of ATP from MSCs as it has been shown to also regulate ATP release in other cell types, including bone [8,9]. The observation that shockwaves or ATP increased P2X7 receptor expression led the authors to suggest a "feed forward mechanism to control bone homeostasis."…”
Section: Commentarymentioning
confidence: 99%
“…This might result in impaired bone formation, as the phenotype of P2Y2 (ATP-binding) receptor-KO mice showed increased bone mass, whereas P2Y13 (ADP-binding) receptor-and adenosine receptor-KO mice showed low bone mass with altered osteoblast differentiation and osteoclast activation (13). If these complex phenotypes are considered together, with a focus on ALP activity, it could be hypothesized that substrate accumulation, notably PPi, inhibits bone mineralization and that ADP/adenosine deficiency further contributes to compromised bone formation with a low-turnover bone phenotype (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%